Methylome of Fetal and Maternal Monocytes and Macrophages at the Feto-Maternal Interface - Kim, Sun Young (2012)
PROBLEM: Decidual macrophages (dMϕ) of the mother and placental macrophages (Hofbauer cells, HC) of the fetus are deployed at a critical location: the feto-maternal interface. This study was conducted to compare DNA methylome of maternal and fetal monocytes, dMϕ, and HC, and thereby to determine the immunobiological importance of DNA methylation in pregnancy. METHODS OF STUDY: Paired samples were obtained from normal pregnant women at term not in labor and their own neonates. Maternal monocytes (MM) and fetal monocytes (FM) were isolated from peripheral blood of mothers and from fetal cord blood, respectively. dMϕ and HC were obtained from the decidua of fetal membranes and placenta, respectively. DNA methylation profiling was done using the Illumina Infinium Human Methylation27 BeadChip. Quantitative real-time PCR and western blot were performed for validation experiments. RESULTS: 1) Significant differences in DNA methylation were found in each comparison (MM vs. FM, 65 loci; dMϕ vs. HC, 266 loci; MM vs. dMϕ, 199 loci; FM vs. HC, 1,030 loci). 2) Many of the immune response-related genes were hypermethylated in fetal cells (FM and HC) compared to maternal cells (MM and dMϕ). 3) Genes encoding markers of classical macrophage activation were hypermethylated and genes encoding alternative macrophage activation were hypomethylated in dMϕ and HC compared to MM and FM, respectively. 4) mRNA expressions of DNMT1, DNMT3A, and DNMT3B were significantly lower in dMϕ than in HC. 5) 5-azacytidine treatment increased expression of INCA1 in dMϕ. CONCLUSIONS: The findings herein indicate that DNA methylation patterns change during monocyte-macrophage differentiation at the feto-maternal interface. It is also suggested that DNA methylation is an important component of biological machinery conferring an anti-inflammatory phenotype to macrophages at the feto-maternal interface.